The Blackwell Companion to the Qur’an - Livnat Holtzman (International Institute of Islamic Thought, 2009)
With The Blackwell Companion to the Qur’an,Andrew Rippin, an illustrious scholar in the field of Qur’anic studies, presents yet another impressive contribution to previous collections of articles on the Qur’an that he has edited: Approaches to the History of the Interpretation of the Qur’an (Oxford University Press: 1988); The Qur’an: Formative Interpretations (Variorum: 1999); and, with Khaleel Mohammed, Coming to Terms with the Qur’an: A Volume in Honor of Issa Boullata (Islamic Publications International: 2008), just to name a few. Gathering the works of scholars from leading universities throughout the world, Rippin has constructed a volume that is designed not only for the general reader “who may have little exposure to the Qur’an beyond a curiosity evoked by the popular media” (p. x), but also to scholars specializing in the Qur’an. The overall aim of this large volume, which comprises thirty-two articles, is to guide the reader to “a well-advanced state of understanding the complexities of the text and its associated traditions” (ibid) ...